The Importance of RBI in the Indian Economy - Dr. Veer Virendra Singh (International Journal of Engineering and Management Research, 2020)
The present economic conditions in many countries worldwide are greatly affected by setbacks. Examples include conflicts, worldwide economic downturn, decrease in economic expansion, and unpredictability resulting from the pandemic. Both growth and inflation face threats from ongoing conflict and sanctions, as well as high oil and commodity prices, prolonged supply chain disruptions, increased global financial market volatility due to changes in monetary policy in major economies, and new outbreaks in India. Most industries experienced a rise in the interest rates of their current loans. With the help of both traditional and non-traditional liquidity tools, the RBI has assisted banks in upholding orderly market conditions and improving sentiment in the financial markets. Given the current situation, the study thoroughly analyzes the patterns of tools utilized by RBI for regulating deposit flow and money circulation within banks, aiming to mitigate adverse impacts of economic downturn. This paper aims to assess the influence of RBI's financial instruments on the Indian economy. The article delves deeper into the impact of specific tools (Repo Rate, Reverse Repo Rate, Cash Reserve Ratio) on Inflation rate, GDP, and Unemployment rate. The research is focused on descriptive study. The research paper heavily relies on World Bank data as the primary secondary source gathered from RBI.